Encounters between Foreign Relations Law and International Law Bridges and Boundaries - Philipp Aust, Helmut; Kleinlein, Thomas (Social Sciences, 2021)
This book offers fresh perspectives on the encounters between foreign relations law and public international law. These can occur in a hybrid zone of interaction which requires both bridges and boundaries. A timely book with crucial relevance for scholars, students and practitioners in both foreign relations law and international law.